Aplikasi Membaca Huruf Hijaiyah Berbasis Android Untuk Anak Usia Dini Sebagai Penerapan Lampung Mengaji - Setiawan, Tajudin; Apriadi, Novi; Amsir, Rojani (JELTec (Journal of Learning Technology), 2024)
Learning to read Hijaiyah letters is a fundamental step in the process of studying the Qur'an. However, for early childhood learners, conventional teaching methods often fail to engage and motivate them effectively. This study aims to develop an interactive and educational Android-based application to assist young children in recognizing and reading Hijaiyah letters. The application is designed to be child-friendly by incorporating audiovisual elements, animations, and interactive exercises tailored to early learners. Additionally, the application serves as a digital implementation of the Lampung Mengaji program, a regional initiative aimed at enhancing Qur'anic literacy from an early age. The research adopts a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results indicate that the application effectively improves children's interest and ability in reading Hijaiyah letters. Therefore, it is expected that this application can become an innovative learning tool that supports the digitalization of the Lampung Mengaji initiative